Insights into current physical, chemical and hybrid technologies used for the treatment of wastewater contaminated with pharmaceuticals. (10th August 2022) - Ghazal, Heba; Koumaki, Elena; Hoslett, John; Malamis, Simos; Katsou, Evina; Barcelo, Damia; Jouhara, Hussam
Abstract: The purpose of this article is to review the current physical, chemical and hybrid technologies practices employed in the removal of pharmaceuticals from liquid effluents originating from various resources including municipal waste, hospitals discharge with a focus on pharmaceutical manufacturing industry. Pharmaceutical pollutants are mostly persistent organic compounds that are not easily removed by conventional wastewater treatment processes. The literature reviewed shows that advanced oxidation processes are able to degrade these persistent pharmaceuticals. However, the oxidation may also introduce toxic oxidation intermediates/by-products if these processes are not properly monitored and operated. Physical treatments, like carbon adsorption and membrane filtration, can provide a barrier that prevents both parent compounds and toxic intermediates passing into treated wastewater. However, these processes are phase changing technologies in which contaminants are transferred from one phase to another hence, the retentate water and absorbent require further treatment, and properly managed disposal. The combination of different processes can be an ideal treatment scheme, for the retention and degradation of both parent and transformation compounds. Through hybrid technologies, the advantages of the methods are combined, leading to a maximization of contaminants removal. The review highlights the importance of installing combined wastewater treatment processes to reduce the amounts of pharmaceutical residues before the wastewater enters the environment. The use of advanced oxidation process, either as a pre-treatment or as a post-treatment combined with biological, adsorption, or filtration process is recommended as a promising option. Nevertheless, the optimum treatment methods for the pharmaceuticals-containing wastewater depends on the quality and quantity of wastewater, as well as on the pharmaceutical compounds residues and their hazardous effects. Graphical abstract: Image 1 Highlights: Evidence of pharmaceuticals including antibiotics in aquatic environment. Physicochemical processes have high removal efficiency and short treatment duration. AOPs and their combination with physicochemical processes are promising options. Hybrid technology can provide a solution for pharmaceutical wastewater treatment.